Risk for Misdiagnosing Chronic Traumatic Encephalopathy in Men With Anger Control Problems - Iverson, Grant L.; Gardner, Andrew J. (Frontiers in Neurology, 2020)
Background: There are no validated or agreed upon criteria for diagnosing chronic traumatic encephalopathy (CTE) in a living person. In recent years, it has been proposed that anger dyscontrol represents a behavioral clinical phenotype of CTE. This is the first study to examine the specificity of the diagnostic research criteria for traumatic encephalopathy syndrome (TES, the clinical condition proposed to be CTE) in men from the United States general population who have anger dyscontrol problems. It was hypothesized that a substantial percentage of these men would meet the research criteria for TES. Methods: Data from 4,139 men who participated in the National Comorbidity Survey Replication, an in-person survey that examined the prevalence and correlates of mental disorders in the United States, were included in this study. Men who were diagnosed with intermittent explosive disorder in the past year were the clinical sample of interest (n=206; 5.0% of all men in the database), and the remaining men were used as a comparison sample. They were classified as meeting research criteria for TES if they presented with the purported supportive clinical features of CTE (e.g., impulsivity/substance abuse, anxiety, apathy, suicidality, headache). Results: In this sample of men from the general population with intermittent explosive disorder, 27.3% met a conservative definition of the proposed research criteria for CTE (i.e., traumatic encephalopathy syndrome). If one assumes the delayed-onset criterion is present, meaning that the men in the sample are compared to former athletes or military veterans presenting with mental health problems years after retirement, then 65.0% of this sample would meet the research criteria for TES. Conclusions: These results have important implications. Using conservative criteria, at least one in four men from the general population, who have serious anger control problems, will meet symptom criteria for TES. If one considers former athletes and military veterans with anger control problems who present many years after retirement, and who experienced a documented decline in their mental health, nearly two-thirds will meet these research criteria. More research is needed to examine risks for misdiagnosing TES and to determine whether anger dyscontrol is a clinical phenotype of CTE.